Factors affecting young Chinese women's intentions to uptake human papillomavirus vaccination: an extension of the theory of planned behavior model - Li Li; Jinhui Li (Taylor & Francis Group, 2020)
Background Aside from personal beliefs, women's intention to uptake human papillomavirus vaccination can be influenced by their perceived risks of developing cervical cancer and daily communication. Objectives This study incorporated perceived risks and communication factors (i.e., media attention and interpersonal discussion) with theory of planned behavioral factors (i.e., attitude, subjective norm, and perceived behavioral control) to predict women's intentions to uptake human papillomavirus vaccination in China. Methods A quantitative survey was conducted with 417 female university students in China. The Structural Equation Modeling analysis was applied to test the proposed extended TPB model and to examine the hypotheses in Mplus software. Results The results showed that the original theory of planned behavior factors and the perceived risk toward cervical cancer were positively related to their intention to uptake human papillomavirus vaccination. Moreover, media attention and interpersonal discussion positively affected people's attitudes toward human papillomavirus vaccination and subjective norm, which further influenced their intentions to uptake human papillomavirus vaccination. Conclusion This study can help better understand unvaccinated eligible vaccine recipients and identify the differences between individuals who are likely and unlikely to get vaccinated.